2022
DOI: 10.21203/rs.3.rs-1803141/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors associated with COVID-19 booster vaccine willingness among migrants from the Eastern Mediterranean living in Australia: a cross-sectional study

Abstract: Background Migrants have been disproportionally affected by COVID-19 in Australia. Vaccination against COVID-19 is a key pillar of Australia's public health response, but little is known about the willingness to receive booster vaccinations among migrants. This study aimed to assess the factors associated with a willingness to receive a COVID-19 booster vaccine among migrants living in Australia born in the World Health Organization’s Eastern Mediterranean Region (EMRO). Methods A cross-sectional survey was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This approach allows for educating the public about vaccination's advantages and potential risks (31). Distressing news affects willingness to receive COVID-19 booster doses, and effective messaging and dissemination are crucial for increased acceptance (32). Prior studies have shown that vaccine hesitancy stems from sociocultural factors, distrust in government authorities (33), individual, and group influences, and misinformation about vaccines (34).…”
Section: Discussionmentioning
confidence: 99%
“…This approach allows for educating the public about vaccination's advantages and potential risks (31). Distressing news affects willingness to receive COVID-19 booster doses, and effective messaging and dissemination are crucial for increased acceptance (32). Prior studies have shown that vaccine hesitancy stems from sociocultural factors, distrust in government authorities (33), individual, and group influences, and misinformation about vaccines (34).…”
Section: Discussionmentioning
confidence: 99%